Perubahan tata guna lahan kampung Prawirotaman kota Yogyakarta sebagai dampak keberadaan kawasan komersial - Nino Ardhiansyah; Dhyah Ayu Retno Widyastuti; Elisabet Dita Septiari (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Culture has a very important essence in people's lives. Values that lead to culture seem to be the “breath” for the survival of society. A well-developed culture that can be viewed from both physical and non-physical aspects inherited from generation to generation becomes a tradition that has strong local wisdom. Yet along with its development, its existence may undergo a shift. This condition may exist because of the presence of other cultures that intentionally brought by or unintentionally emerge along with the presence of immigrants. This study aims to identify the shifts of cultural values of the people in Prawirotaman Village, especially in the aspect of community economic activities, through several stages such as: (1) Mapping changes in residential spatial planning in Prawirotaman Village; (2) Exploring economic activities changes in Prawirotaman Village. The results of the study indicate a change in governance and use of land in Prawirotaman Village. This change indeed has implications to socio-economic activities and most particularly to economic or livelihood system. © 2019 Nino Ardhiansyah, Dhyah Ayu Retno Widyastuti, Elisabet Dita Septiari